In vitro ischemia-induced changes in the transcriptome of hippocampal neurons: neuroprotective pathways in brain ischemia - Fernandes, Joana Filipa Coelho (2014)
Tese de doutoramento em Ciências e Tecnologias da Saúde (Pré-Bolonha), especialidade de Biologia Celular e Molecular, apresentadas à Faculdade de Farmácia da Universidade de Coimbra